The pirating musician: an examination into the attitudes and justifications toward music piracy among musicians - Yeoh, Joanne Pei Sze; Yeoh, Pei Ann (Global Science and Technology Forum, 2014)
Research on music piracy has always been conducted among non-musicians. This study sets out to investigate two aspects: (1) the intentions toward pirating music among undergraduate music students us-ing the Theory of Planned Behaviour, and (2) how rationalizations justify their ac-tions. A quantitative study looking at 200 music students across music colleges and universities in Malaysia was carried out in attempt to evaluate theory claims. Results show that the intention to pirate music is significantly related to perceived behav-ioural controls. More importantly, the re-sults show that music students admit to piracy without having a need to justify their criminal activity.